ARCHITECTURE OF INTERNATIONAL FINANCING FOR UKRAINE’S RECOVERY - Matvievsky, Nazar (Public Management and Policy, 2026)
Ukraine’s post-war recovery creates an unprecedented demand for investment and budget support, but available financing channels differ in cost, conditionality, mobilisation speed and fiscal implications. An additional constraint is the need to align the investment cycle with budget rules, transparency and accountability of fund use. The study aims to build an applied financing-gap model based on RDNA4 needs estimates and to develop a matrix of international financial instruments suitable for selecting a financing mix under scenarios of resource availability and debt sustainability constraints. A scenario framework is proposed where the average annual need is derived from the total need divided by the assessment horizon, and the financing gap is computed as the difference between the need and the sum of external and domestic resources. Using demonstrative parameters, three scenarios are constructed, illustrating the shift from near-balanced financing to a systemic deficit that requires sector prioritisation and phased reconstruction. An instrument matrix (grants, concessional IFI loans, state guarantees, blended finance, war-risk insurance/risk-sharing, and public-private partnerships) is developed with application conditions, key risks and control indicators to align the “gap – instrument – control” logic within a single investment cycle. The minimum preconditions for implementing the mechanism are outlined (priority project portfolio, debt framework, selection rules, monitoring and audit). The effectiveness of international financing is determined not by the list of sources but by the architecture of their combination: budget support should be complemented by private capital mobilisation and risk-premium reduction tools, while fiscal rules, transparency and stage-gated project selection are necessary conditions for a viable recovery portfolio. The proposed approach can serve as an analytical template for configuring financing programmes and monitoring recovery performance.